Hubungan Dukungan Sosial Keluarga Terhadap Motivasi Diri Pasien Stroke Yang Melakukan Rehabilitasi Fisioterapi Di RSU Haji Medan - Mhd. Choiril Fitra Bangun; Trisno Susilo; Lagut Sutandra (LPPM STIKES Siti Hajar dan Insight Power, 2023)
Background: Family support is very important for patients because the healing process of stroke patients takes a relatively long time, it needs deep understanding and patience from all parties, especially families, the family is expected to talk and interact with stroke patients at all times because psychologically, the motivation is very strong. For sufferers to express something, it will encourage their ability to speak and move/act (Setiadi, 2009 in Nugraha, 2016). Objective: This study aims to see how the family relationship to the motivation of stroke patients to do physiotherapy at Haji Hospital Medan. Methods: This study used a cross sectional approach with a purposive sampling technique of sampling. Results: Based on the test, it was found that the hypothesis test above was found to be 0.000 where the number was smaller than 0.05, so it can be concluded that there is a relationship between family support and self-motivation of stroke patients. Conclusion: It is hoped that the family can fully support the patient in doing therapy in the hospital in order to increase the patient's self-motivation to recover. Keywords: Family Support, Self Motivation, Stroke.